Prevalensi obesitas dengan perawakan pendek pada anak SD Negeri 2 Dangin Puri Kota Denpasar tahun 2017 - Aditya Permana Adriyanto; I Gusti Ayu Widianti; I Nyoman Gede Wardana (Bali Anatomy Journal, 2018)
Obesity is a range of body weight greater than the normal weight range for a certain height and short stature/stunting is a condition where height by age is below the third percentile of the WHO growth curve. The incidence of obesity and short stature is quite high in Indonesia, but data in Indonesia that discuss about obesity with short stature is still small. The purpose of this study is to determine the prevalence of obesity with short stature in elementary school children 2 Dangin Puri Denpasar City in 2017. This study is a cross sectional descriptive study conducted in SD Negeri 2 Dangin Puri Denpasar City. The data obtained is the result of direct measurement on the students by measuring body weight, height and age. Data were analyzed using Microsoft Excel program and CDC 2000 growth curve. The results showed that from the 614 children, 97 children (15.8%) were obese, 67 children (10.91%) had overweight and 61 children (9.94%) had short stature. Children with obesity with short stature amounted to 1 child (0.16%) and who were overweight with short stature amounted to 3 children (0.49%).